Factors That Influence Mothers In Early Breastfeeding In Polindes Temuan Sari Musi Rawas District - Bayanti, Anggi Nur; Rohani, Tuti; Umami, Desi Aulia (Universitas Dehasen Bengkulu, 2024)
Inappropriate provision of early complementary feeding not only disrupts the nutritional intake that babies should receive, but also disrupts the baby's digestion because the digestive system is not yet able to digest or break down the food. The coverage of exclusive breastfeeding in infants aged 0-6 months in the Working Area of the Findingsari Village Health Center, Musi Rawas Regency is still low. The purpose of this study was to determine the factors for providing early complementary feeding in infants aged 0-6 months in the Working Area of the Findingsari Village Health Center, Musi Rawas Regency.The design of this study is descriptive analytical with a cross-sectional approach. The sample of this study was all mothers who had babies aged (0-6) months who were in the working area of the Findingsari Village Health Center, Musi Rawas Regency, totaling 63 people. This study used univariate and bivariate analysis. The results of the univariate analysis of this study showed that from 63 respondents, almost all (49.2%) had a supportive attitude, more than half (54.0%) were working, almost all (44.4%) whose husbands supported and more than half (61.9%) who provided Early MP ASI. The results of the bivariate analysis obtained attitudes with a value of p = 0.001 ≤ α = 0.05, mother's job with a value of p = 0.005 ≤ α = 0.05 and husband's support with a value of p = 0.007 ≤ α = 0.05. Results research This show variable attitude most big relate with provision of early complementary feeding for babies aged 0-6 months at the Findingsari Village Health Center, Musi Rawas Regency. It is hoped that the health center will increase the dissemination of information through counseling to society through role cadres to increase knowledge about the importance of providing exclusive breastfeeding.